Post-operative glioblastoma multiforme segmentation with uncertainty estimation - Holtzman Gazit, Michal; Faran, Rachel; Stepovoy, Kirill; Peles, Oren; Shamir, Reuben Ruby (Frontiers in Human Neuroscience, 2022)
Segmentation of postoperative GBM is essential for the planning of Tumor Treating Fields (TTFields) treatment and other clinical applications. Recent methods developed for preoperative GBM segmentation perform poorly on postoperative GBM MRI scans. In this paper we present a method for the segmentation of GBM in postoperative patients. Our method incorporates an ensemble of segmentation networks and the Kullback–Leibler divergence agreement score in the objective function to estimate the prediction label uncertainty and cope with noisy labels and inter-observer variability. Moreover, our method integrates the surgery type and computes non-tumorous tissue delineation to automatically segment the tumor. We trained and validated our method on a dataset of 340 enhanced T1 MRI scans of patients that were treated with TTFields (270 and 70 train and test set sizes, respectively). For validation, we developed a tool that uses the uncertainty map along with the segmentation result. Our tool allows visualization and fast editing of the tissues to improve the results dependent on user preference. Three physicians reviewed and graded our segmentation and editing tool on 12 different MRI scans. The validation set average (SD) Dice scores were 0.81 (0.11), 0.71 (0.24), 0.64 (0.25), 0.68 (0.19) for whole-tumor, resection, necrotic-core and enhancing-tissue, respectively. The physicians rated 72% of the segmented GBMs acceptable for treatment planning or better. Another 22% can be edited manually in a reasonable time to achieve a clinically acceptable result. According to these results, the proposed method for GBM segmentation can be integrated into TTFields treatment planning software in order to shorten the planning process. To conclude, we have extended a state-of-the-art preoperative GBM segmentation method with surgery-type, anatomical information and uncertainty visualization to facilitate a clinically-viable segmentation of postoperative GBM for TTFields treatment planning.